Market Power, Price Adjustment, and Inflation - Allen Head; Alok Kumar; Beverly Lapham (Queen's University, Department of Economics, 2006)
We study the responses of real and nominal prices to random flutuations in costs and money growth using a monetary search economy in which there are no costs or temporal restrictions on sellers' ability to change prices. The economy exhibits a form of price stickiness in that the price level may react incompletely to either type of shock as a result of endogenous changes in the average mark-up driven by movements in consumers' search intensity. The average mark-up falls as inflation rises, a finding consistent with emprical observations. As a result of this reduction in market power, prices become more responsive to shocks as inflation rises. Our results are consistent with empirical findings that the degree of price adjustment in response to both cost and money growth shocks is increasing in the average rate of inflation, that the variance of inflation increases with its average level, and that positive and negative shocks to money growth have asymmetric effects.
Keywords: E31; D43; E42; 330; Search; Mark-up; Inflation; Price Dispersion; Pass-through; Monetäre Wachstumstheorie; Marktmacht; Suchtheorie; Produktivität; Geldmenge; Mark-up Pricing; Inflation; Theorie